PENGAWETAN EMPAT JENIS KAYU UNTUK TIANG LISTRIK DENGAN METODA SEL PENUH - Emmy Yetty; Barly Barly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
A full cell treatment of four wood species with 5 and 7 percent copper-chrome-arcenic solution was conducted using small samples of 18-25 cm in diametre and 30 cm long. The cross cut-ends of the samples were coated to prevent penetration of the preservative through these parts. The preservation process were held for 2 and 4 hours at a pressure of 8 and 10 atmosphere. The result of the test revealed that four wood species (keluntum, medang, manggung and puspa) are recommended for power poles servation. The treatment shchedule proposed for four wood species is presented in this paper.